PERENCANAAN DEEP LEARNING DALAM KEGIATAN BELAJAR SETIAP HARI DI TK SOLIDEO MAULAFA - Witin, Mariaana; Kale, Sartika; Simbolon, Gallex; Novyani Seran, Theodorina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The importance of developing critical thinking skills in early childhood has been widely discussed in educational theory. However, in practice, many early childhood education institutions still apply conventional learning methods such as memorization and an emphasis on basic literacy and numeracy. Therefore, a deep learning approach is needed, whose implementation highly depends on teachers’ ability to plan learning activities systematically, purposefully, and in accordance with children’s developmental needs. This study aimed to describe the planning of deep learning in daily learning activities at TK Solideo Maulafa. This study employed a descriptive qualitative method. Data were collected through observation, semi-structured interviews, and documentation involving one principal and three classroom teachers. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and conclusion drawing. Data validity was ensured through technique triangulation and source triangulation. The results showed that deep learning planning at TK Solideo Maulafa was implemented through four main indicators: (1) identifying students’ readiness, material characteristics, and graduate profiles; (2) designing learning objectives and learning frameworks including pedagogical practices, partnerships, learning environments, and the use of digital technology; (3) designing learning experiences based on the principles of mindfulness, meaningfulness, and joyful learning through the stages of understanding, applying, and reflecting; and (4) conducting formative and summative assessments outlined in the Deep Learning Lesson Plan (RPM). This study indicates that deep learning planning at TK Solideo Maulafa has been implemented systematically in accordance with the Academic Manuscript of Deep Learning by the Indonesian Ministry of Education (2025), and it may serve as a reference for other early childhood education institutions.